Pengaruh Mineral Pada Foliasi Terhadap Sifat Fisik dan Mekanik Batuan Metamorf di Daerah Bayat, Klaten, Jawa Tengah - Pratama, Gilang Rizki; Ediyanto, Ediyanto (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
Bayat area is a place where one of the three oldest rock outcrops in Java is Pre-Tertiary and Paleogene age. Due to its geological conditions and relatively old age, the Bayat area is exposed to many distinctive metamorphic rocks. These rocks include rocks including marble, schist, phyllite, serpentinite, quartzite of Pre-Tertiary age, siltstone, sandstone, limestone, and igneous rocks including gabbro intrusions, basalt, and micro diorite. Foliated metamorphic rocks have a diversity of mineralogical, petrographic characteristics, and engineering properties. The results from 3 types of schist, namely mica schist, green schist, and graphite schist, show that the mechanical strength of the samples is generally the result of various parameters, such as foliation angle, mineral type, mineral size, and degree of weathering. The dominant minerals that comprise these three types of schist are mica, chlorite, quartz, k-feldspar and actinolite. The compressive strength test of the rock used the Point load index test method with the results of the compressive strength of green schist being 10.34 Mpa, mica schist being 4.66 Mpa, and graphite schist being 6.74. Linear regression correlation analysis is used to determine the magnitude of the correlation coefficient between mineral parameters and compressive strength so as to know how big the relationship between the two is and produce certainty of the correlation.